Thomas Hirschhorn : Deleuze monument - Dezeuze, Anna (One work., 2014)
"Thomas Hirschhorn's Deleuze monument was conceived for 'La beauté' in Avignon in 2000. It comprised four elements: a rock inscribed with a quotation, an altar, a monumental sculpture and a library including books by and about Deleuze. Located in the Cité Champfleury, outside Avignon's historical walls, Deleuze monument embodied Hirschhorn's desire to put his work 'in a difficult situation' between reality, politics and aesthetics, and marks a significant turning point in his approach to producing and maintaining public works"--Page 4 of cover.